Numerical simulation of magnetic-aligned compaction with pulsed high magnetic field. (15th July 2016) - Soda, Rikio; Takagi, Kenta; Ozaki, Kimihiro
Abstract: A three-dimensional discrete element method capable of handling ferromagnetic particles was developed to enable computer simulation of powder metallurgic processes for the production of bulk magnets, and was applied to the magnetic-aligned compaction process with a pulsed high magnetic field which we proposed. The simulation results showed that the pulsed-magnetic field causes a decrease in contact force due to particle rearrangement. This decrease was experimentally confirmed as a decrease in compaction pressure, thus verifying the developed simulation model is capable of predicting the motion peculiar to magnetic particles. Graphical abstract: Highlights: We develop a particle-based simulation technique for permanent magnet particles. Numerical model with magnetic hysteresis and anisotropy is proposed. Motion of permanent magnet particles under a pulsed-magnetic field is visualized by the simulation model.